Prevalence of latent TB infection and TB disease among adolescents in high TB burden countries in Africa: a systematic review protocol. Issue 3 (10th March 2017) - Bunyasi, Erick Wekesa; Schmidt, Bey-Marrie; Abdullahi, Leila Hussein; Mulenga, Humphrey; Tameris, Michele; Luabeya, Angelique; Shenje, Justin; Scriba, Thomas; Geldenhuys, Hennie; Wood, Robin; Hatherill, Mark
Abstract : Introduction: Almost a third of the world population has latent tuberculosis (TB) infection (LTBI), ∼10 million of whom develop TB disease annually, despite existence of effective, but lengthy, preventive and curative drug regimens. Although adolescents appear to have a very high force of LTBI, their reported incidence of TB disease is less than that of their corresponding general population. The few available studies on adolescent TB infection and disease prevalence are not sufficient to address the apparent discordance between rates of infection and disease in high TB burden countries in Africa. Therefore, we aim to perform a systematic review to examine the relationship between adolescent LTBI and TB disease, benchmarked against national TB disease burden data. Methods and analysis: A comprehensive literature search will be performed for cross-sectional studies and screening data in cohort studies to determine the prevalence of LTBI and TB disease among adolescents in high TB burden countries in Africa in the following databases: PubMed, Scopus, Cochrane library, Web of Science, Africa Wide, CINAHL and the Africa Index Medicus . This will be supplemented by a search of reference lists of selected articles for potentially relevant articles. We will restrict our search to articles published in the English language between 1990 and 2016 among adolescents in order to obtain estimates reflective of the mature HIV epidemic in most high TB burden countries in Africa that occurred over this critical period. Primary end points are: prevalence of LTBI and TB disease. We will use the random-effects or fixed-effects modelling for our meta-analysis based on heterogeneity estimates. Ethics and dissemination: No ethics approval is required given that this is a systematic review. Findings will be disseminated in a peer-reviewed journal in line with the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA). Trial registration number: CRD42015023495.